2015
DOI: 10.1115/1.4030734
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prediffuser Angle on the Static Pressure Recovery in Flow Through Casing-Liner Annulus of a Gas Turbine Combustor at Various Swirl Levels

Abstract: A numerical study has been performed in an axisymmetric diffuser followed by a casing-liner annulus of a typical gas turbine combustor to analyze the flow structure and pressure recovery in the geometry. Static pressure recovery in a gas turbine combustor is important to ensure high pressure of air around the liner. However, the irreversible pressure losses reduce the static pressure recovery from the ideal value. The presence of swirl in the flow from compressor and prediffuser geometry before the dump diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Unfortunately, as the ame temperature of a fuel and air admixture is decreased to approximately 1500°C, typically combustion becomes unstable and high carbon monoxide emissions are generated [11,12]. Therefore, legal compliance requirements placed on both nitrogen oxides and carbon monoxide make the operating window for a lean, premixed combustor quite limited [13,14], even operating at rich enough conditions where nitrogen oxides levels are as high as 15 or 20 milligrams per cubic meter.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, as the ame temperature of a fuel and air admixture is decreased to approximately 1500°C, typically combustion becomes unstable and high carbon monoxide emissions are generated [11,12]. Therefore, legal compliance requirements placed on both nitrogen oxides and carbon monoxide make the operating window for a lean, premixed combustor quite limited [13,14], even operating at rich enough conditions where nitrogen oxides levels are as high as 15 or 20 milligrams per cubic meter.…”
Section: Introductionmentioning
confidence: 99%
“…Too higher values of it lead to flow separation on its wall, as per the results of Ghose et al (2016). At lower magnitudes of PDA such as 12°, 18°, from Klein (1995), it is clear that losses at 18° are higher than those at 12°.…”
Section: Computational Domainmentioning
confidence: 76%
“…They have mentioned the important requirements of the liner wall and casing wall pressure distributions. Ghose et al (2016) have studied numerically, the effect of pre-diffuser angle (PDA) on the liner wall and casing wall pressure variation, with and without inlet swirl. They have considered 4 pre-diffuser angles which are 0°, 12°, 27°, and 50°.…”
Section: Fig 1 Diffuser Types Faired Diffuser (B) Dumpmentioning
confidence: 99%
See 1 more Smart Citation
“…It is concluded that in addition to the dump gap ratio, the aerodynamic shape of the flame tube case and the other geometric variables are also needed to be optimized judiciously after considering the fluid dynamic constraints for controlling the pressure recovery and the losses. Ghose et al [21] have studied the effects of different prediffuser angles, inlet swirl levels, and different dump gaps on the streamline distribution and the static pressure recovery coefficients. They observed that the dump gap has significant influence on the static pressure recovery only at small prediffuser angle.…”
Section: Introductionmentioning
confidence: 99%